'We ain't got no drink, Pa' : the heart breaking true story of a little girl's struggle to survive in the slums of 1920-30s East London /: the heart breaking true story of a little girl's struggle to survive in the slums of 1920-30s East London. (2015) - Kemp, Hilda; Kemp, Cathryn
No abstract available